Insights Into Nicotinic Receptor Signaling in Nicotine Addiction: Implications for Prevention and Treatment - Liu, Wuyi; Li, Ming D. (Current Neuropharmacology, 2018)
Background: Nicotinic acetylcholine receptors (nAChRs) belong to the Cys-loop ligandgated ion-channel (LGIC) superfamily, which also includes the GABA, glycine, and serotonin receptors. Many nAChR subunits have been identified and shown to be involved in signal transduction on binding to them of either the neurotransmitter acetylcholine or exogenous ligands such as nicotine. The nAChRs are pentameric assemblies of homologous subunits surrounding a central pore that gates cation flux, and they are expressed at neuromuscular junctions throughout the nervous system. Methods and Results: Because different nAChR subunits assemble into a variety of pharmacologically distinct receptor subtypes, and different nAChRs are implicated in various physiological functions and pathophysiological conditions, nAChRs represent potential molecular targets for drug addiction and medical therapeutic research. This review intends to provide insights into recent advances in nAChR signaling, considering the subtypes and subunits of nAChRs and their roles in nicotinic cholinergic systems, including structure, diversity, functional allosteric modulation, targeted knockout mutations, and rare variations of specific subunits, and the potency and functional effects of mutations by focusing on their effects on nicotine addiction (NA) and smoking cessation (SC). Furthermore, we review the possible mechanisms of action of nAChRs in NA and SC based on our current knowledge. Conclusion: Understanding these cellular and molecular mechanisms will lead to better translational and therapeutic operations and outcomes for the prevention and treatment of NA and other drug addictions, as well as chronic diseases, such as Alzheimer's and Parkinson's. Finally, we put forward some suggestions and recommendations for therapy and treatment of NA and other chronic diseases.
Keywords: smoking-related diseases